2012
DOI: 10.1111/odi.12040
|View full text |Cite
|
Sign up to set email alerts
|

Oral leukoplakia in a South African sample: a clinicopathological study

Abstract: DEDICATIONThis thesis is dedicated to my parents for their belief in me, to my wife for her unconditional love and support and to my daughter.iii ABSTRACT Oral leukoplakia is the most common potentially malignant oral lesion. While the clinicopathological features in white patients are well characterised, this is not the case in black people. The aim of this study is to analyse the differences in the clinicopathological features of oral leukoplakia in different racial groups in the greater Johannesburg area of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
5
6
2
3
Order By: Relevance
“…This study revealed that OL was more frequent in males than females, and this was consistent with the majority of reports in the literature. In the Sudan, smoking and Toombak dipping habits remain socially unaccepted among females, a fact that explains the greater number of cases of OL who are male.…”
Section: Discussionsupporting
confidence: 91%
“…This study revealed that OL was more frequent in males than females, and this was consistent with the majority of reports in the literature. In the Sudan, smoking and Toombak dipping habits remain socially unaccepted among females, a fact that explains the greater number of cases of OL who are male.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have reported that men underwent malignant transformation more frequently than women [15,16]. In the present study, the expansion of lesion and malignant transformation were more frequent in men than in women.…”
Section: Discussioncontrasting
confidence: 46%
“…Several studies have evaluated the clinicopathological factors predictive of malignant transformation in patients with oral leukoplakia and demonstrated significant differences in age, gender, cite of lesion, size of lesion, number of sites affected, and clinical and pathological appearance of the lesions [12][13][14][15][16][17][18][19]. In the present study, the lesions that were non-homogenous and located on the tongue presented with a higher grade were likely to progress into cancer.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…[32,34] However, it has become clear that the histopathological information gained from multiple biopsies taken from different parts of the invasive front of the cancer has a more significant prognostic value. [35] In the population of greater Johannesburg in South Africa, oral leukoplakia occurs significantly more frequently in white than in black persons, [17,36] but as this study shows that black and white persons are affected by OSCC more or less equally, it is reasonable to assume that in Johannesburg, OSCC develops de novo more frequently in blacks than in whites. This suggests that in some way the pathogenesis of OSCC may be different in black and white persons.…”
Section: Sd = Standard Deviationmentioning
confidence: 98%